2022
DOI: 10.3389/fnagi.2021.772136
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Brain Activity of Inferior Temporal Region Increased in Prodromal Alzheimer's Disease With Hearing Loss

Abstract: Background and ObjectiveHearing loss (HL) is one of the modifiable risk factors for Alzheimer's disease (AD). However, the underlying mechanism behind HL in AD remains elusive. A possible mechanism is cognitive load hypothesis, which postulates that over-processing of degraded auditory signals in the auditory cortex leads to deficits in other cognitive functions. Given mild cognitive impairment (MCI) is a prodromal stage of AD, untangling the association between HL and MCI might provide insights for potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The vascular etiology is an important part of the disease process, 79 such as the hypoperfusion and dysfunction of blood brain barrier 80 . Additionally, visual and auditory impairments have been found in MCI or AD patients and correlate with cognitive function 81,82 . Moreover, it is clear that the gut‐brain axis plays a vital role in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular etiology is an important part of the disease process, 79 such as the hypoperfusion and dysfunction of blood brain barrier 80 . Additionally, visual and auditory impairments have been found in MCI or AD patients and correlate with cognitive function 81,82 . Moreover, it is clear that the gut‐brain axis plays a vital role in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…80 Additionally, visual and auditory impairments have been found in MCI or AD patients and correlate with cognitive function. 81,82 Moreover, it is clear that the gut-brain axis plays a vital role in neurodegenerative diseases. And constipation has been considered to be a factor of cognitive decline in AD and MCI patients.…”
Section: Increased Bfcs Fc Was Correlated With Better Cognitive Funct...mentioning
confidence: 99%
“…The ‘cognitive load’ hypothesis attempts to explain the relationship between hearing loss and cognition as a function of cognitive resources necessary when someone is training to hear and process degraded auditory signals, which may lead to deficits in other cognitive functions. Hong et al [27] conducted a prospective study attempting to explore this relationship using functional magnetic resonance imaging and cognitive scores. Their study identified an interactive effect between hearing loss and cognitive status; those with cognitive impairment demonstrated decreased spontaneous activity in the auditory cortex and increased activity in regions used to process visuospatial information and multimodal sensory integration.…”
Section: Hearing Loss and Cognitionmentioning
confidence: 99%